Molecular effects of gliding - Scherge, M.; Böttcher, R. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: This contribution summarizes 10 years of research with respect to gliding phenomena of nordic skis. The focus was put on the interplay of ski sole preparation and friction. Commencing from a broad literature overview, issues like grinding, waxing, structuring, and brushing will be addressed.